2018
DOI: 10.12677/ap.2018.81001
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Aging Stereotype on the Memory in the Elderly: A Review

Abstract: This article summarized the research on aging memory in the past 20 years about the impact of aging stereotypes on the memory of the elderly, from differences in old age stereotype impressions, whether they can be perceived, the type of stimuli, and the different aspects of the regulatory variables. As a result, we found that positive stereotypes can promote and improve the memory of the elderly, and the negative stereotypes can inhibit and reduce the memory of the elderly. The influence of the image stimulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…Negative aging stereotypes as a social cognitive factor have a negative impact on older adults that cannot be ignored. Research has found that aging stereotypes have a significant impact on people's physiology, cognition, behavior, and daily life (He et al, 2013;Bae et al, 2018;Chiviacowsky et al, 2018;Li and Xu, 2018). For example, aging stereotypes can affect individuals' physiological functions, such as blood pressure, hearing (Levy et al, 2000a(Levy et al, , 2009, cognitive functions such as memory performance and judgment (Wheeler and Petty, 2001;O'Brien and Hummert, 2006;Radvansky et al, 2010), and everyday habits such as writing and reading, and consumption behavior (Bargh et al, 1996;Levy et al, 2000a;Bae et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Negative aging stereotypes as a social cognitive factor have a negative impact on older adults that cannot be ignored. Research has found that aging stereotypes have a significant impact on people's physiology, cognition, behavior, and daily life (He et al, 2013;Bae et al, 2018;Chiviacowsky et al, 2018;Li and Xu, 2018). For example, aging stereotypes can affect individuals' physiological functions, such as blood pressure, hearing (Levy et al, 2000a(Levy et al, , 2009, cognitive functions such as memory performance and judgment (Wheeler and Petty, 2001;O'Brien and Hummert, 2006;Radvansky et al, 2010), and everyday habits such as writing and reading, and consumption behavior (Bargh et al, 1996;Levy et al, 2000a;Bae et al, 2018).…”
Section: Introductionmentioning
confidence: 99%